The Coupling of Stride Length and Foot Strike in Running - Thompson, Missy; Hoffman, Kristine; Blythe, Lindsay; Hasler, Rachel; Longtain, Megan (Frontiers in Sports and Active Living, 2022)
Modifying stride length and/or footstrike in running results in mechanical alterations associated with injury risk. Stride length and footstrike have often been treated as independent factors that affect running mechanics, but there is evidence to suggest that they may be coupled. The purpose of this study was to examine the relationship between footstrike and stride length in running, and to determine if these variables are coupled and if so, can be independently manipulated? Fifteen individuals ran over ground with stride lengths +/- 10 % of their preferred stride length while adopting both a fore/mid foot strike and rear foot strike pattern, as well as running with their self-selected stride length and footstrike when the opposite variable was controlled. Three-dimensional motion capture and force plate data were captured synchronously during the manipulated stride length x footstrike trials. The results indicate that footstrike and stride length are coupled, with shorter stride lengths being associated with a F/MFS and longer stride lengths being associated with a RFS pattern. Impact peak magnitude was primarily dependent on footstrike, with a F/MFS pattern reducing the magnitude of the impact peak force regardless of stride length. Peak vertical and horizontal ground reaction forces were found to be primarily dependent on stride length, with longer stride lengths resulting in increased vertical and horizontal ground reaction forces, regardless of footstrike. It is difficult, but possible, to independently manipulate stride length and footstrike. Clinicians should be aware of the coupled changes in stride length and footstrike.